2012
DOI: 10.1186/1868-7083-4-10
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 methylation in visceral adipose tissue of severely obese individuals is associated with metabolic syndrome status and related phenotypes

Abstract: BackgroundEpigenetic mechanisms may be involved in the regulation of genes found to be differentially expressed in the visceral adipose tissue (VAT) of severely obese subjects with (MetS+) versus without (MetS-) metabolic syndrome (MetS). Long interspersed nuclear element 1 (LINE-1) elements DNA methylation levels (%meth) in blood, a marker of global DNA methylation, have recently been associated with fasting glucose, blood lipids, heart diseases and stroke.AimTo test whether LINE-1%meth levels in VAT are asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 54 publications
5
54
0
Order By: Relevance
“…Furthermore, recent studies have demonstrated a relationship between DNA methylation and metabolic diseases, such as obesity [21]. Therefore, the methylation levels of the promoter region in the following genes IL6 , LINE1 , SERPINE1, and TNF , previously linked with this type of pathological conditions [21,31,32,33,37,38,39], were evaluated in obese subjects with SAHS, in order to examine the molecular links between resting oxygen consumption and chronic diseases. Methylation levels of IL6 and SERPINE1 were positively associated with FFM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies have demonstrated a relationship between DNA methylation and metabolic diseases, such as obesity [21]. Therefore, the methylation levels of the promoter region in the following genes IL6 , LINE1 , SERPINE1, and TNF , previously linked with this type of pathological conditions [21,31,32,33,37,38,39], were evaluated in obese subjects with SAHS, in order to examine the molecular links between resting oxygen consumption and chronic diseases. Methylation levels of IL6 and SERPINE1 were positively associated with FFM.…”
Section: Discussionmentioning
confidence: 99%
“…Several polymerase chain reaction (PCR)-based methods have been used in order to easily analyze DNA methylation from leukocytes. In this context, global DNA methylation has been assessed measuring the methylation of CpG islands in the promoter region of the long interspersed nucleotide element 1 ( LINE1 ) retrotransposon [30,31,32,33], the only active, autonomous transposable element in humans [34]. Besides, some studies have investigated the relation between methylation pattern of genes with obesity, metabolic disturbances, and aging [27,28,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of DNA methylation patterns have been associated with various diseases, including cancers and cardiovascular diseases (Wernimont et al, 2011;DelgadoCruzata et al, 2012). Lower global DNA methylation has been observed in individuals with severe metabolic syndrome (Turcot et al, 2012). Patients with vascular disease exhibit increased plasma total Hcy (tHcy) and decreased genomic DNA methylation (Castro et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…BMI and obesity have been associated with differential DNA methylation of immortalized lymphocytes and leukocytes, respectively [35,36]. Global DNA methylation, analyzed by measuring methylation of the repetitive LINE-1 element in visceral adipose tissue of obese subjects, was further associated with glucose levels and status of the metabolic syndrome [37]. Moreover, caloric restriction for 6 months induced epigenetic changes and coordinate changes in gene expression in adipose tissue of overweight and/or obese women [38].…”
Section: Non-genetic Risk Factors and Epigenetic Modifications In Tarmentioning
confidence: 99%